Pengaruh Beban Kerja dan Stres Kerja Terhadap Kinerja Pegawai pada Biro Pembangunan dan Lingkungan Hidup Pemprov DKI Jakarta: The Effect of Workload and Work Stress on the Performance of Employees of the Development and Environment Bureau of the DKI Jakarta Provincial Government - Nur Rahma Dina; Nurzalinar Joesah; Supriatin Supriatin (CV Warnak Johanna Nusantara, 2026)
The research was conducted at the DKI Jakarta Provincial Government's Development and Environment Bureau with the aim of assessing the relationship between workload and job stress on employee performance. The approach applied was a quantitative method using statistical tools. The research data came from primary data, while the sample determination used a saturation technique. The analysis stages involved descriptive, data quality assessment, classical assumption testing, hypothesis testing, and calculating the coefficient of determination. The results of the analysis indicated that both workload and job stress partially contributed a significant impact on employee performance, as evidenced by the value (Sig.) of 0.002 for workload and 0.032 for job stress, both of which were smaller than 0.05. Furthermore, the results of the simultaneous analysis also confirmed a significant effect, indicated by the F value of 0.002. Based on this, it was concluded that the workload (X1) and job stress (X2) variables had a significant positive impact on employee performance (Y), both individually and combined, because the value (Sig.) of both met the criteria ≤ 0.05.